Signage design - Galindo, Michelle ([Salenstein, Switzerland] : Braun, 2012)
"This volume showcases 111 current examples of signage design from across the world, indoors and outdoors. These cover a wide range of typologies, from individual buildings like museums, schools and airports to larger contexts such as traffic navigation systems."--Jacket.
Includes index.
Keywords: Signs and signboards -- Pictorial works; Graphic design (Typography); Communication in design; Signs and signboards -- Design